The Indian Economy: Up to 1991 and Since - Kaushik Basu (BREAD Working Paper No. 052, 2003)
Since the reforms of the early nineties, the Indian economy seems to have performed well and has raised expectations of a major take off. The paper evaluates the historical background of this improved performance and also the sluggishness of the first 30 years of independent India, laying emphasis on the social norms, beliefs and culture in which every economy is inevitably embedded.